Exploring the association between parenting stress and a child's exposure to adverse childhood experiences (ACEs). (July 2019) - Crouch, Elizabeth; Radcliff, Elizabeth; Brown, Monique; Hung, Peiyin
Abstract: Nearly half of U.S. children age 0–17 have been exposed to adverse childhood experiences (ACEs), accounting for over 34 million of children nationwide. Parenting stress (negative feelings related to the demands of parenting) is a primary risk factor for child maltreatment and neglect; yet has been an overlooked factor for ACEs. Understanding the degree of parenting stress and its subsequent associations with ACEs will facilitate future designations of relevant interventions to keep children safe. We analyzed 2016 data from the National Survey of Children's Health to examine whether increased levels of parenting stress are associated with higher counts of ACEs among children. About 4.4% of caregivers reported "high parenting stress" and children living with them were three times more likely (OR: 3.05; 95% CI: 2.23–4.15) to experience four or more ACEs by the age of 18. Lowering parenting stress through parenting interventions could decrease the level of childhood trauma experienced by a child or may lessen one type of stress in a home where many other stressors exist. Highlights: Parenting stress, negative feelings related to the demands of parenting, is a primary risk factor for child maltreatment and neglect. The quantification of parenting stress and its subsequent association with ACEs is important to determine because of the significant negative impact ACEs may have on a child's long-term physical, emotional, and social well-being. Lowering parenting stress could influence the level of childhood trauma a child might experience.